An investigation into the bacterial biosynthetic origins of bioactive natural products isolated from South African latrunculid sponges - Waterworth, Samantha Che (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Several pyrroloiminoquinone alkaloids exhibiting cytotoxic, anti-tumour activity have been isolated from sponges within the Latrunculiidae family that are endemic to the South African coastline. Other, structurally similar pyrroloiminoquinone compounds have been isolated from geographically distant and phylogenetically distinct marine sponges, as well as terrestrial myxomycetes which suggested that sponge-associated bacteria may be the true biosynthetic origin of pyrroloiminoquinone compounds. Previous studies have shown that there is conservation of spirochete and betaproteobacterial species in the bacterial communities associated with South African Latrunculiidae sponges and it was proposed that these conserved bacteria represented candidate pyrroloiminoquinone-producers. This study aimed to confirm the conserved dominance of betaproteobacteria and spirochetes within bacterial communities associated with South African latrunculid sponges and employed a shotgun metagenomic approach to assess the functional and biosynthetic potential of associated microbiota in Tsitsikamma favus sponges. Clustering of assembled contigs revealed twenty-three putative bacterial genomes, of which, two were identified as representatives of the conserved betaproteobacteria and spirochete species previously identified in Tsitsikamma sponges. It was shown that the spirochete was most likely an obligate symbiont that benefitted the host sponge through possible defence against pathogenic bacteria and/or nutrient acquisition. The putative genome representing the conserved betaproteobacteria was found to be heavily contaminated and further sequencing is required to accurately resolve the genome for functional characterization. Several biosynthetic gene clusters were identified and demonstrated the bioactive potential of Tsitsikamma favus-associated bacteria. A biosynthetic gene cluster was identified on an unclustered contig that included several genetic features that were indicative of possible pyrroloiminoquinone production.
Keywords: Marine biodiversity; Metagenomics; Sponges -- Biotechnology; Spirochetes; Natural products -- Biotechnology